Gewalt gegen Männer in Partnerschaften Eine empirische Untersuchung zur Situation in Deutschland - Schemmel, Jonas (Edition Seehaus [plus] - Resozialisierung - Opferschutz - Restorative Justice, 2024)
There is a lack of scientifically collected data on intimate partner violence against men in Germany. The authors present findings from a quantitative, representative online survey of 1,200 men aged 18-69 on the prevalence of partner violence, its consequences, men's experiences with the support system and individual risk factors, and a qualitative interview study with 16 men who were interviewed in detail about their experiences. Finally, the study reports the results of an expert workshop in the form of recommendations and a special analysis of the Lower Saxony survey on partner violence among 15-year-old male adolescents.